Spreadsheet modeling and decison analysis : a practical introduction to management science - Ragsdale, Cliff T., 1960- (South-Western College, 2001)
Introduction to modeling and decision analysis. Introduction to optimization and linear programming. Modeling and solving LP problems in a spreadsheet. Sensitivity analysis and the simplex method. Network modeling. Integer linear programming. Goal programming and multiple objective optimization...